Pembuatan Cairan Eco-Enzyme sebagai Solusi Pengelolaan Sampah Organik Rumah Tangga melalui Teknologi Shred-Chopper di Desa Tapanrejo Banyuwangi - Setyawan, Bagus; Utami, Arfiati Ulfa; Defriatno, Mawan Eko (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Tapanrejo Village is located in Muncar Sub-district with a large area and high population density. This village experiences problems with household waste generation, which is dominated by organic waste. This amount of waste is further increased by the presence of agricultural waste which is the result of community activities. Therefore, the solution applied to this problem is to utilize household organic waste which is processed into eco-enzyme liquid. The partners of this activity are mothers from the Tapanrejo Village Family Empowerment and Welfare Movement Team (TP-PKK). The purpose of implementing this program is that partners are able to manage household waste independently and are able to make eco-enzyme liquid with the application of a shred-chopper machine to improve the quality of life of the community. The stages of activity in this program consist of the stages of socialization, mentoring and direct practice. Monitoring and evaluation of the results of community service activities are carried out by assessing the success of participants in making eco-enzyme liquids and distributing questionnaires of satisfaction with the implementation of activities filled in by each participant. This community service activity begins with the implementation of socialization and training in making eco-enzyme liquids, implementing shred-chopper machines for waste shredding, and monitoring the evaluation of activities based on questionnaires filled out by activity participants. The implementation of the activity went well and the women participating in the activity were very enthusiastic about participating in the training from start to finish. Based on the results of the activity, 100% of the participants were able to make eco-enzyme liquid according to the instructions given and based on the satisfaction questionnaire that 80% of the participants were very satisfied with the implementation of socialization and training on household waste management and making eco-enzyme liquid that had been given.